How does the tea L-theanine buffer stress and anxiety - Liwen Wang; Margaret Brennan; Shiming Li; Hui Zhao; Klaus W. Lange; Charles Brennan (Food Science and Human Wellness)
Tea (Camellia sinensis) is widely considered to promote feelings of calming and soothing. This effect is attributed to L-theanine (L-γ-glutamylethylamide) in tea, a non-protein amino acid mainly derived from tea leaves. As a naturally occurring structural analogue of glutamate, L-theanine competes for the receptors with glutamate and is able to pass the blood-brain barrier to exert its relaxation effect. This review focuses on the relaxation effect of L-theanine, including animal models and the latest human trials as well as the potential molecular mechanisms regarding neuron stem cells. The biological efficacy of dietary L-theanine in the food matrix has been further discussed in this review in relation to the physiological changes in the gastrointestinal tract and bindings of L-theanine with other food components.